HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN OBESITAS PADA GURU SMP NEGERI 3 TANJUNG MORAWA KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2016 - Rani Ulfa Lubis; Zulhaida Lubis; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Nutritient problem is one of society problem which is never complete to ward off in the world. Nutritient problem tackling has not been handled era of nutritient transition that increase obesity incident. Based on profil data of Indonesian healthy that experience in 2014 adult inhabitant percentage in North Sumatera provincereach percentage 18,09% in obesity. Eating behavior pattern with high energy supply and low out of put of energy can cause obesity problem. The objective of this research is to know the relationship between eating behavior and physical activity with obesity of SMP Negeri 3 Tanjung Morawa teacher in Tanjung Morawa subdistrict Deli Serdang district year 2016. Type of research isused quantitative research eith research design of cross sectional descriptive observasional. Population of this research is all teacher of SMP Negeri 3 Tanjung Morawa. Data is obtained by interview result by using Dietary History Method and direct measurement of body high and also body weighing. Data analize include univariate and bivariate analyze. Research result show that teacher frequency distribution of obesity about 61,9%. Kind of food relate with obesity (p=0,008; RP=5,000), energy sufficiency (p=0,001; RP=14,000), carbohydrate sufficiency (p=0,016; RP 0,529), fat sufficiency (p=0,049; RP=3,000) related with obesity. Protein sufficiency does not relate with obesity (p=0,100; RP=0,800). Physic activity relate with obesity (p=0,031; RP=1,717). Factors relate of obesity are kind of food, energy sufficiency, carbohydrate sufficiency, fat sufficiency and physic activity. Factor does not relate of besity is protein sufficiency (p=0,100; RP=0,800).Suggested to the teachers who are obese, it would be better to decrease body weight pay attention to food supply in daily life. Observing the changing of body weihgting by individual is very suggested. Routine sport to deciease body weight and keep body healthy. School should make routine schadule to sport for teacher or held sport competition with some kinds of sport to increase physical teacher activity. Keywords: Eating Pattern, Physical Activity, Teachers Obesity.